PENTINGNYA KESADARAN HUKUM DALAM DINAMIKA SOSIAL DI MASYARAKAT - Arya Salman Aziz, Surya Wira Yudhayana, dan (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2024)
Compliance with legal consciousness in society is an integral aspect of legal culture, reflecting in daily actions aligned with applicable regulations for legal entities. This compliance is evident through adherence to rules in daily life and group contexts, as well as the emergence of legal awareness due to fear of legal consequences. It reflects respect for the rules and legal norms governing social interactions. The importance of compliance with legal consciousness in society signifies recognition of the need for order and justice in social relations. When individuals and social groups obey the law, it creates a more stable and secure environment for all members. Moreover, compliance with the law also provides a strong foundation for sustainable social development by creating conditions conducive to harmonious and inclusive progress. Therefore, fostering legal consciousness should be a primary focus of governments and relevant institutions through education, fair law enforcement, and easy access to the justice system. Thus, legal consciousness can become a cornerstone in building a society based on the values of justice, peace, and sustainable progress.